2006
DOI: 10.1584/jpestics.31.123
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of ELISA in pesticide monitoring to control runoff of bensulfuron-methyl and simetryn from paddy fields

Abstract: The applicability of ELISA kits was evaluated as an alternative to monitor bensulfuron-methyl and simetryn behavior in paddy water under intermittent (Plot 1) and continuous (Plot 2) irrigation schemes. Simetryn concentrations in both plots decreased exponentially from the peak of the first day. However, the simetryn kit systematically underestimated by a factor of 0.79 as compared to the GC method. Bensulfuron-methyl concentrations exhibited similar dissipation kinetics in paddy water and the drainage water. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…The influence of temperature on pesticide fate during the two rice crop seasons in the actual paddy field is difficult to assess due to combined effects of multiple factors including water level, precipitation, percolation, and seepage rates (Watanabe et al 2006(Watanabe et al , 2007. Moreover, field experiments are usually expensive and labor intensive; hence alternative methods to assist in the investigation of pesticide fate in rice paddies are required.…”
mentioning
confidence: 99%
“…The influence of temperature on pesticide fate during the two rice crop seasons in the actual paddy field is difficult to assess due to combined effects of multiple factors including water level, precipitation, percolation, and seepage rates (Watanabe et al 2006(Watanabe et al , 2007. Moreover, field experiments are usually expensive and labor intensive; hence alternative methods to assist in the investigation of pesticide fate in rice paddies are required.…”
mentioning
confidence: 99%
“…Risk management for reducing pesticide runoff losses from paddy fields Water management is a key practice for controlling pesticide runoff from the paddy fields. As indicated previously, pesticide concentration is significant in the earlier period and drainage control in this period is crucial for controlling the pesticide runoff 7,24,34,36,38,39 . As reported in those studies, a continuous irrigation-drainage scheme seems to result in significant pesticide runoff losses (e.g.…”
Section: Application Of Mathematical Models To High Tier Risk Assessmmentioning
confidence: 84%
“…38% and 49% of total mefenacet and bensulfuron-methyl losses, respectively 36 ). Meanwhile, the importance of water management practices such as a water holding period and its practical method for reducing pesticide runoff loss from paddy fields has been discussed 24,30,36,38,39 . The length of the water holding period after pesticide application was evaluated using PCPF-1 simulations for the herbicide mefenacet runoff loss from paddy fields for a continuous irrigation-drainage scheme with water holding periods of 0 day (WH-0), 4 days (WH-4), 10 days (WH-10), 21 days (WH-21), and 30 days (WH-30) as presented in Fig.…”
Section: Application Of Mathematical Models To High Tier Risk Assessmmentioning
confidence: 99%
“…The triazine herbicide, simetryn (N 2 , N 4 -diethyl-6-methylthio-1,3,5-triazine-2,4-diamine) is popular in Japan and is often detected in high concentrations in rivers and lake waters (Nohara and Iwakuma 1996;Kibe et al 2000;Sudo et al 2004;Watanabe et al 2006). It has been reported that simetryn in river water affects the phytoplankton community directly through growth inhibition (Okamura et al 2002) and often decreases zooplankton density through indirect effects resulting from reduced algal productivity, thus affecting their food supply (Kasai and Hanazato 1995).…”
Section: Introductionmentioning
confidence: 99%